White king : a novel [large type] - Gómez-Jurado, Juan (Thorndike Press large print high octane., 2025)
"The Red Queen project is under attack on all fronts. Across Europe, its agents are murdering each other and cases from the past, long believed resolved, are rearing their deadly heads again. At the center of it is the mysterious Mr. White, who has been weaving a web around Antonia for a very long time. He is as smart and capable as her but, unlike her, he's a psychotic killer who has isolated Antonia Scott." --